Building Research Capacity in Higher Education: Exploring Confidence as a Mediator of Contextual Support and Research Interest - Zubair Ahmad (4345072) (2025)
Building research capacity in higher education depends significantly on understanding the various contextual support systems that influence and shape students' research interests. This study aims to explore the relationship between these support systems such as universities, tutors, and families and the research interests of STEM undergraduates, particularly concerning their academic confidence. Grounded in the Situated Expectancy-Value Theory (SEVT), this study examines how different dimensions of support contribute to a student's interest in research. The paper begins with a thorough literature review of factors affecting research interest in STEM fields, followed by a detailed presentation of the study's conceptual framework. Methodologically, the study is conducted in two stages. The first phase involves developing and validating instruments to measure the relevant constructs. The second phase applies Structural Equation Modeling (SEM) using AMOS software to test the proposed relationships among these constructs, including a cross-validation process. The results indicate that all constructs are unidimensional, with academic confidence fully mediating the relationship between tutor support and research interest. Additionally, confidence partially mediates the effects of family and university support on research interest. As a result, undergraduate confidence is identified as a crucial mediator that may bridge the gap between contextual support and the research interests of STEM undergraduates. Other Information Published in: Innovative Higher Education License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10755-025-09823-y